Порівняльний аналіз структурної організації яєчок щурів в віковому аспекті - Пастухова, В.А. (Таврический медико-биологический вестник, 2009)
В данной работе изучали особенности структурной организации яичек крыс разных

возрастных периодов. Выявлено, что в семенниках половонезрелых животных

происходят активные процессы размножения и роста клеток сперматогенного

ряда, а с возрастом происходит угасание как сперматогенной, так и

гормонопродуцирующей функций яичек. In this investigation the peculiarities of the rats’ testicles structure organization of the

different growth periods were studied. It was revealed, that processes of the active

reproduction of the cells of the spermatogenic row and their growth are going on in

the testicles of the sexual-not-grown animals and during animals are becoming aged

the spermatogenic and hormonogenic functions of the testicles are going down.